HDAC4 stabilizes SIRT1 via sumoylation SIRT1 to delay cellular senescence. (January 2016) - Han, Xiaolin; Niu, Jing; Zhao, Yang; Kong, Qingsheng; Tong, Tanjun; Han, Limin
Summary: The nicotinamide adenine dinucleotide‐dependent protein deacetylase silent information regulator 2 (Sir2) regulates cellular lifespan in several organisms. Histone deacetylase 4 (HDAC4) belongs to the class IIa group of HDACs; this class of HDACs is composed of proteins that are important regulators of gene expression that control pleiotropic cellular functions. However, the role of HDAC4 in cellular senescence is still unknown. This study shows that the expression patterns of HDAC4 and Sirtuin 1 (SIRT1; the mammalian homolog of Sir2) are positively correlated during cellular senescence. Moreover, the overexpression of HDAC4 delays senescence, whereas the knockdown of HDAC4 leads to premature senescence in human fibroblasts. Furthermore, it is demonstrated that HDAC4 increases endogenous SIRT1 expression by enhancing its sumoylation modification levels, thereby stabilizing its protein levels. This study, therefore, provides a new molecular mechanism for the regulation of cellular senescence.